Every Rose Has Its Thorns - How Exemplars Manage the Tensions in Inclusive Leadership - Zheng, Wei (Journal of business ethics, 2025)
In our increasingly polarizing world, inclusive leadership practices that aim to foster belongingness and uniqueness for all organizational members become essential to individual and organizational thriving. However, according to optimal distinctiveness theory, inclusive efforts may involve managing the tension between meeting the needs for belongingness and uniqueness, which can be compounded in contexts with diverse representations of subgroups. This tension has received limited attention in the conceptualization of inclusive leadership, which constrains further theory development. To better understand this issue, we interviewed 39 exemplary inclusive leaders to identify how they experience and manage potential tensions underlying inclusive leadership practices. Our findings reveal three tensions underlying the pull toward diversification and that toward integration, as experienced by these exemplars of inclusive leadership: (1) seeking divergence vs. seeking similarities, (2) providing differential support vs. providing equal support; and (3) encouraging subgroups vs. encouraging connections across subgroups. This research provides a new lens that views inclusive leadership practices as the management of tension-filled practices that celebrate diverse people and perspectives while seeking similarities to rally members, that correct disparities among subgroups while ensuring support for everyone, and that provide comfortable enclaves for similar people while connecting dissimilar people across subgroups. Based on our findings, we provide theoretical implications for future theoretical extensions, refinement, and measurement of inclusive leadership, as well as practical implications on how to develop inclusive leaders.